Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1097/00006199-199907000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Burden Experienced by Caregivers of Relatives with Dementia in Taiwan

Abstract: The Burden Model tested in this study corroborates findings from other burden studies and extends our knowledge of caregiver burden. Filial obligation, self-efficacy, demands of care, involvement in care, and coping were shown to predict burden in this sample of Taiwanese caregivers. Future study is needed to evaluate interventions designed for family caregivers of persons with dementia. Especially needed is research in the area of counseling and mental health services to assist caregivers in dealing with mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
2
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 48 publications
13
126
2
7
Order By: Relevance
“…In the Chinese society and other Asian countries, there is an obligation to care for a dependent older relative that is influenced by cultural values and filial responsibility (Chou, LaMontagne & Hepworth 1999;Choi 1993). Recent family studies have shown that Effectiveness of mutual support group 6 such belief of filial obligation often causes a heavy burden for family caregivers, which can be progressively overwhelming (Li & Bucchel 2007;Almberg, Grafstman & Winbald 1997).…”
Section: Cultural Considerations For Family Support and Carementioning
confidence: 99%
See 2 more Smart Citations
“…In the Chinese society and other Asian countries, there is an obligation to care for a dependent older relative that is influenced by cultural values and filial responsibility (Chou, LaMontagne & Hepworth 1999;Choi 1993). Recent family studies have shown that Effectiveness of mutual support group 6 such belief of filial obligation often causes a heavy burden for family caregivers, which can be progressively overwhelming (Li & Bucchel 2007;Almberg, Grafstman & Winbald 1997).…”
Section: Cultural Considerations For Family Support and Carementioning
confidence: 99%
“…Families are expected to care for their dependent elders at home. Many Chinese families are dominated by Confucianistic principles, with a belief in showing respect, filial piety and obligation to care for an elder and a strong emphasis on specific roles and proper relationships among the family members (Chou et al 1999), are expected to take care of their older family members at home. This is also particularly true for Chinese women such as wife, daughter, and daughter-in-law, because of the culturally defined gender roles in which women are believed to be fully responsible to provide family care (Chien 2005;Fung & Chien 2002).…”
Section: Cultural Considerations For Family Support and Carementioning
confidence: 99%
See 1 more Smart Citation
“…The internal consistency reliability of this scale was .73 and evidence for concurrent validity includes a correlation of .62 with a filial obligation measure based on role tasks (Cicirelli, 1983). The Mandarin version of the scale had a Cronbach's alpha value of .88 in a sample of family caregivers living in Taiwan (Chou, LaMontagne, & Hepworth, 1999).…”
Section: Quantitative Instruments and Analysismentioning
confidence: 86%
“…Denney (78) y Chou et al (79) revisaron la eficiencia del cuidado suministrado, las demandas del mismo, la autoeficacia al cuidar y las estrategias de afrontamiento.…”
Section: Factores De Desgasteunclassified